Pengaruh Budaya Organisasi Komitmen Organisasi dan Motivasi terhadap Kinerja Pegawai Kantor Camat Pandan Kabupaten Tapanuli Tengah - Henni Wardina; Ali Borkat Hasibuan; Khairul Anwar Panggabean; Mega Sari Yanti Siregar (Jurnal Prodi Fakultas Ekonomi-UISU, 2022)
This formula research internal issue is how influence of organizational culture, organizational commitment and motivation on employee performance. The purpose of this study was to determine and analyze the influence of organizational culture on employee performance. To find out and analyze the effect of organizational commitment on employee performance. To find out and analyze the effect of work motivation on employee performance. To determine and analyze the influence of organizational culture, organizational commitment and motivation on employee performance. The sample in this study amounted to 32 people. The data analysis technique used in this research is multiple linear regression analysis. The results of this study explain that organizational culture has a positive and significant effect on employee performance. Organizational commitment has a positive and significant effect on employee performance. Work motivation has a positive and insignificant effect on employee performance. Organizational culture, organizational commitment and motivation have a positive and significant effect on employee performance.